Ethnic networks and the location choice of migrants in Europe - Klaus Nowotny; Dieter Pennerstorfer (University of Salzburg, Department of Social Sciences and Economics, 2012)
This paper analyzes the role of ethnic networks in the location decision of migrants to the EU at the regional level. Using a random parameters logit specification we find a substantially positive effect of ethnic networks on the location decision of migrants. Furthermore, we find evidence of spatial spillovers in the effect of ethnic networks. Analyzing the trade-off between potential income and network size, we find that migrants would require a sizable compensation for living in a region with a smaller ethnic network, especially when considering regions where only few previous migrants from the same country of origin are located.
Keywords: F22; R23; C35; 330; Network migration; ethnic networks; random parameters logit